Analysis of the Influence of Risk Perception of the Generation Z on Investment Interest in the Digital Era (Study on Economics Students of the 2021 Cohort in Malang City) - Rosela Lini Rohi; Ahmad Mukoffi; Rizka Aprilia Dwi Susanti (International Journal of Management and Business, 2025)
This study aims to analyze the effect of risk perception on investment interest of Generation Z, especially in Economics students of class of 2021 in Malang City, Method: This study uses a quantitative approach with a survey method. Data were collected using a questionnaire that measures risk perception, including financial, market, technology, and data security risks, as well as investment interest. The research sample consisted of 70 respondents selected by simple random sampling, Data analysis: The analysis technique used is multiple linear regression, with a t-test to test the partial effect between variables, independent of the dependent variable, Results and discussion: The results of the study indicate that risk perception has a significant effect on investment interest of Generation Z. A better understanding of risk can increase investment interest, with financial education, investment experience, and access to information also playing a role. Digital literacy has also been shown to increase confidence in making investment decisions, Conclusion: This study concludes that risk perception affects investment interest of Generation Z. Therefore, it is recommended to improve financial education, better access to information, and digital literacy so that Generation Z can invest more wisely and intelligently.